SrLaGa3O7:Bi3+/Eu3+/Tb3+: A novel trichromatic phosphor for WLEDs. Issue 2 (15th January 2023) - Li, Zhi-Jian; Wang, Xu-Ping; Yu, Hua-Jian; Qiu, Cheng-Cheng; Zhang, Yuan-Yuan; Li, Jing; Lv, Xian-Shun; Liu, Bing; Shi, Qiang; Yang, Yu-Guo
Abstract: In order to improve the properties of white light-emitting diodes (WLEDs), a number of phosphors have been investigated. In this study, a variety of SLGO phosphors doped with Bi 3+ /Eu 3+, Bi 3+ /Tb 3+, and Bi 3+ /Eu 3+ /Tb 3+ ions were synthesized by the solid-state reaction method. The crystal structure, site occupancy of the SLGO host, and the phase composition of the synthesized phosphors were discussed. The optical properties of the synthesized phosphors were characterized by UV–vis, PLE and PL techniques. The relative PL mechanisms and energy transfer (ET) processes (Bi 3+ →Eu 3+, Bi 3+ →Tb 3+ and Tb 3+ →Eu 3+ ) were discussed in detail. In addition, the CIE chromaticity coordinates of these phosphors were calculated. Tunable PL has been achieved througth adjusting the concentrations of three doping ions and ET process. The ET process was verified by the fluorescence lifetime test. The thermal stability of the phosphor was also studied and discussed. Finally, a WLED device was fabricated by combining the SLGO:Bi 3+ /Tb 3+ /Eu 3+ phosphor with a 275 nm LED chip, and the electroluminescence was measured. The values of CCT and CRI were 5263 K and 78, respectively. The results demonstrate that the synthesized phopshors have potential applications in the field of WLEDs.